Who Replaced the Intellectual in the Democratic Transition? - Avramović, Zoran M. (Sociološki pregled, 2019)
The paper analyzes the social and political processes that have led to a radical change in the role of intellectuals in society. What is happening with intellectuals in Western European societies is also recognizable in the so-called transition countries which include Serbia: their public role is to retreat before other actors. As the meaning of the public and the public good changes, so does the notion of intelligentsia. The paper highlights the strengthening of the public role of political parties, participants in electronic and print communication, civic movements. The newly created circumstances of social and political life marginalize the former role of intelligentsia as the voice of the public, as a social group articulating the interests and needs of peoples and citizens. Public good advocates are no longer needed. The final part analyzes the changes in the public role of intelligentsia in Serbia.
Keywords: intelligentsia; transition; political parties; media; civic movements; Serbia